Diseño e implementación del sistema contable comercial para el depósito de colas y cervezas Barcelona, cantón La Maná, provincia de Cotopaxi, año 2013 - Morales Moya, Gissela Elizabeth (2015)
Commercial accounting in conjunction with the accounting system is necessary and important tools for the development of the accounting process in the hold of Soft Drinks and Beers Barcelona, La Mana Canton, Cotopaxi Province, can be said that this accounting tool being used in the management of companies selling products, in order to improve the standards of sales and profitability in the company. The research conducted allows knowing the movements of each of the products to their customers. In the development of this research with their respective proposal was used descriptive and exploratory research that has led to better relate to the research with the investigation.